Routing by matching on convex pieces of grid graphs - Alpert, H.; Barnes, R.; Bell, S.; Mauro, A.; Nevo, N.; Tucker, N.; Yang, H. (Computational geometry : theory and applications, 2022)
The routing number is a graph invariant introduced by Alon, Chung, and Graham in 1994, and it has been studied for trees and other classes of graphs such as hypercubes. It gives the minimum number of routing steps needed to sort a set of distinct tokens, placed one on each vertex, where each routing step swaps a set of disjoint pairs of adjacent tokens. Our main theorem generalizes the known estimate that a rectangular grid graph R with width w(R) and height h(R) satisfies rt(R)∈O(w(R)+h(R)). We show that for the subgraph P of the infinite square lattice enclosed by any convex polygon, we have rt(P)∈O(w(P)+h(P)).